HYPOGLYCAEMIC EFFECT OF MORINGA OLEIFERA AND AZADIRACHTA INDICA IN TYPE 2 DIABETES MELLITUS - D. JALAJA KUMARI (The Bioscan, 2010)
The present study was designed to investigate clinically the hypoglycemic effect of seeds of Moringa oleifera and Azadirachta indica in Type 2 Diabetes Mellitus. About 55 type-2 diabetes (36 men and 19 women) in the age group of 30-60 years were selected from the Hospital of Acharya Nagarjuna University and Diabetic Care hospital, Guntur and divided into two Experimental (n=46) and control group (n=9). The first two experimental were administered Moringa oleifera leaves powder (8gm) and Azadirachta indica seeds powder (6gm) per day respectively in three divided doses for 40 days. The third group of 9 subjects did not receive any treatment and were designated as the control group. There was a significant reduction in fasting blood glucose (p<0.01), the post prandial blood glucose levels (p<0.05) of the subjects in the two groups showed significant reduction, while there was no reduction in the control group. A significant reduction in the mean blood lipid levels of the subjects who were administered the two herbal powders was observed. Among the two herbs selected Moringa oleifera leaves powder was found to be more effective followed by Azadirachta indica seeds powder.